Kebijakan Pengelolaan Lingkungan Hidup dalam Upaya Pemenuhan Perlindungan Hak Lingkungan Masyarakat Desa Kiara Kabupaten Karawang - Wahyu Donri Tinambunan; Muhammad Rusli Arafat; Galih Raka Siwi; Reviansyah Erlianto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Environmental issues in the target municipalities are issues that affect the sustainability of the municipalities' own future development processes, namely waste disposal (environmental management) issues. This activity aims to provide an understanding that a healthy environment is the fulfillment of the rights earned by communities, and the concept of the right to a good environment to develop useful and profitable waste management skills. It is intended to be offered to eligible partners for devotion. and be healthy yourself. The method used consists of a preparation phase, an implementation phase, and a reporting phase. During the implementation phase, Abdimas activities are carried out using socialization and demonstration techniques. Socialization occurs through the engagement of performance goal partners and actively and interactively between resource personnel and participants. The resource officer stressed that a healthy environment is the realization of the rights that communities have earned. In the demonstration, food waste composting technology (Takakura technology) was introduced to reduce waste in the community target area. This Abdimas action went according to plan.